Canine-Assisted Therapy and Quality of Life in People With Alzheimer-Type Dementia: Pilot Study - Leticia Sánchez-Valdeón; Elena Fernández-Martínez; Sara Loma-Ramos; Ana Isabel López-Alonso; Enrique Bayón Darkistade; Valentina Ladera (Frontiers in Psychology, 2019)
BackgroundWith the aim of improving the quality of life of people with Alzheimer’s disease, primarily as regards behavioral and psychological symptoms, we implemented canine-assisted therapy in a group of people with this disease.MethodsWe conducted a quasi-experimental study, with a simple pre-post case series design. Participants comprised 10 Alzheimer’s day care center users presenting severe or very severe cognitive decline. The measurement instrument employed was the Quality of Life in Late-Stage Dementia (QUALID) scale.ResultsBy the end of the therapy, 100% of participants showed an improvement in physical, behavioral, and psychological aspects. The total scores of the QUALID scale for the three different evaluation times (before the therapy and 6 and 12 months after starting) after the canine-assisted therapy intervention were smaller and less dispersed. The total score for the QUALID scale decreased significantly (p < 0.05) at 6 and 12 months after starting therapy. An analysis by item revealed that the scores of all of them fell during the course of the therapy.DiscussionOur study provides evidence of the significant benefits of canine-assisted therapy for quality of life in people with Alzheimer’s disease.